(untitled) (University Heart Journal, 2018)
Chikungunya virus (CHIKV) is an RNA alphavirus of the Togaviridae family that produces an acute febrile illness in humans followed by Joint pain, Itchy rash and leg swelling. This emerging virus has caused several large outbreaks in parts of Africa, Asia, and the Indian Ocean Islands and more recently in the Caribbean. This study was done from December 2015 to November 2016 on 24 confirmed Chikungunya patients with leg swelling. Peripheral vascular duplex study was done in every patients to find out the cause of leg swelling. Unilateral leg swelling 83% and Bilateral leg swelling 17%. Lower limb vascular Duplex was done in all patients. Moderate resersible lymphatic oedema in subcutaneous tissue of lower limb was found in 22 patients only. 2 patients had cellulites with mild lymphatic swelling. DVT was absent. There was mild reduction of peak systolic arterial flow in 13 patients which is secondary to pressure effect of lymphedema and leg swelling. 16 patients had non tender lymphadenopathy (>1cm in diameter), 2 had tender lymphadenopathy in inguinal region and no enlarged lymph glands was observed in rest of the 6 patients. 6 patients had neutropenia and 8 had lymphopenia. Gradual improvement of symptoms was observed with conservative treatment. Lymphedema is reversible and conservative therapy is appropriate. And Non tender lymphadenopathy does not require treatment. University Heart Journal Vol. 13, No. 1, January 2017; 13-16